let-7b/g silencing activates AKT signaling to promote gastric carcinogenesis - Kang, Wei (BioMed Central, 2014)
BACKGROUND: Aberrant AKT activation contributes to gastric cancer cell survival and chemotherapy resistance, however its regulation is poorly understood. microRNAs have been established to be important regulators in gastric carcinogenesis. Here, we showed the functional role and putative target of let-7b and let-7g (let-7b/g) in gastric carcinogenesis. METHODS: The expression of let-7b/g in gastric cancer cell lines and primary tumors were evaluated by miRNA qRT-PCR. The putative target gene of let-7b/g was explored by TargetScan followed by further validation. Functional analyses including MTT proliferation, monolayer colony formation, cell invasion assays and in vivo study were performed in both ectopic expression and knockdown approaches. RESULTS: let-7b/g was found down-regulated in gastric cancer and its downregulation was associated with poor survival and correlated with lymph node metastasis. let-7b/g inhibited AKT2 expression by directly binding to its 3’UTR, reduced p-AKT (S473) activation and suppressed expression of the downstream effector pS6. AKT2 mRNA expression showed negative correlation with the expression of let-7b/g in primary tumors. Short interfering RNA (siRNA) mediated knockdown of AKT2 phenocopied the tumor-suppressive effects of let-7b/g. Moreover, AKT2 re-expression partly abrogated the growth-inhibitory effect of let-7b/g. CONCLUSION: In conclusion, our findings reveal decreased let-7b/g contributes to aberrant AKT activation in gastric tumorigenesis and provide a potential therapeutic strategy for gastric cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-014-0281-3) contains supplementary material, which is available to authorized users.